MON-396 A Critical Review of the Assessment of Vitamin D Status - Chausmer, Arthur B (J Endocr Soc, 2020)
In the United State the evaluation of osteoporosis frequently includes an assessment of vitamin D status. Most often this is done by evaluation of the serum 25 hydroxycalciferol (25 OHD) level. The reasons for this are not entirely clear since D deficiency is characterized by osteomalacia, pathologically very different from osteoporosis. Presumably the reason is to assess the adequacy of calcium absorption across the gastrointestinal mucosa so as to provide sufficient substrate to the osteoid for bone mineralization. If this is the case, the best assessment of D status should be the active metabolite, 1,25 dihydroxycalciferol, (1,25 OH2 D), not an inactive intermediate, such as 25 OHD. The use of an inexact test results in increased cost for less reliable data and supports factitious deficiency with unnecessary and potentially dangerous treatment. The most often quoted reason for not using the 1,25 OH2 D is the short half life. This neglects the fact that half life is not relevant to substances in equilibrium and that the circulating half life does not necessarily reflect the physiologic half life. Equally important, the 25 OHD as a marker of D status is variable due to, among others, drug metabolites affecting hepatic 25 hydroxylases, hepatic function in general, and differences in the activation of of 25 D related to renal function. Additionally, there is virtually no data about the whole body load for any metabolite in the D pathway, so there is no way of actually assessing whether stores are replete or not. While there are several studies suggesting 25 OHD is only a marginal indicator of D status, primarily in the extreme deficiency states which generally rare in the United States. Well controlled studies of the efficacy of 1,25 OH2 D in the assessment of D status are few for many reasons, most prominently cost and lack of sponsor interest. In the absence of such data, one must rely on basic physiologic principals which strongly suggest abandoning the use of the 25 OH D level as an indicator of vitamin D status and, perhaps, using the 1,25 OH2 D to assess D status.